A Rare Case of Osteomyelitis of an Ankle Caused by Mycobacterium chelonae - Lenka Ryskova; Rudolf Kukla; Radka Bolehovska; Libor Prokes; Milan Vajda; Tomas Kucera; Ivo Pavlik; Pavel Bostik; Pavel Ryska (MDPI AG, 2023)
Mycobacterium chelonae, a rapidly growing nontuberculous mycobacterium, is usually described as a causative agent of soft tissue infections (postsurgical, posttraumatic, posttransplantation, postinjection, catheter infection, etc.), but only rarely as a cause of osteomyelitis. The authors describe a case report of a 72-year-old man with osteomyelitis of the talus. Initially, the infection was assessed as a soft tissue infection, without any osteolytic changes on the X-ray. After cultivation with subsequent targeted molecular typing of the rpoB gene, M. chelonae was identified from the affected tissue. The bone involvement was subsequently detected on MRI and confirmed histologically with findings of the granulomatous tissue and acid-fast bacilli. The patient was initially treated intravenously with a combination of tigecycline, amikacin, and moxifloxacin for 4 weeks, after which the oral combination of doxycycline and moxifloxacin continued. Identification of the infecting pathogen using molecular typing thus helped to establish the correct diagnosis and represents a rarely described case of osteomyelitis caused by M. chelonae.